A retrospective cohort study on prognostic factors and anti-thrombotic therapy and its correlation with disease outcome in patients of COVID-19 - Manthan Prajapati; Madhav Oza; Mansi Bhagat; Mrudangsinh M. Rathod; Mehul Ramanbhai Marwadi (SpringerOpen, 2023)
Abstract Background Since the outbreak of coronavirus disease 2019 (COVID-19), many studies have been conducted on clinical features, laboratory parameters, treatment, and anticoagulation therapy. However, there is a scarcity of studies investigating the relationship between prognostic parameters, anti-thrombotic agents, and their impact on disease outcomes within the regional population. A complete analysis of all the factors related to the prognostic, risk, therapies are important to identify the possible interpretation of the disease progression. To find out the utilization of antithrombotic therapy in patients of coronavirus disease 2019 and to study the correlation of antithrombotic therapy and prognostic factors with survival and non-survival. Methods In this retrospective study we included data of coronavirus disease 2019 positive patients who aged more than 18 with or without comorbidities, non-pregnant. We collected data of 768 patients from the medical record department of a tertiary care hospital. For the collected cohort data, we applied descriptive analysis and contingency analysis to find any difference between the surviving and non-surviving group of patients. Results We found that compared to survivors, the age was higher in non-surviving patients. Non-surviving patients had higher D-dimer, C-reactive protein (CRP), lactate dehydrogenase (LDH), and Ferritin levels than survival. The coagulation profile was changed in the non-surviving group. Further conducting contingency analysis, we found the critical role of anti-thrombotic agents in the outcome of the disease. We found that one anti-thrombotic agent has a varied result over another. Co-morbidities were found to be a significant factor for the outcome of the disease; as we analysed, we found diabetes mellitus and hypertension in most non-survivors. Conclusion We found that many prognostic factors were more important in finding the disease progression and can help in the administration of a particular anti-thrombotic therapy.